2006
DOI: 10.2136/sssaj2005.0365
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐Plant System Response to Pulsed Drip Irrigation and Salinity

Abstract: High‐frequency drip irrigation supplies water and nutrients at a rate that is close to plant uptake, thus enhancing growth and production. In light of water scarcity in arid regions, marginal water is increasingly considered as a resource for agricultural production. The objective of this study was to investigate the combined effects of pulsed irrigation and water salinity on the response of the soil–plant system. As a test crop, bell pepper (Capsicum annuum L.) was cultivated in a screenhouse and drip irrigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 25 publications
6
61
1
5
Order By: Relevance
“…Other studies have also reported good performance of this software for various soil, water, and crop conditions under pressurised irrigation systems (e.g., Assouline et al, 2006;Ajdary et al, 2007;Patel and Rajput, 2008;Phogat et al, 2012Phogat et al, , 2013Ramos et al, 2012).…”
Section: Soil Water Distribution and Water Balancementioning
confidence: 73%
See 1 more Smart Citation
“…Other studies have also reported good performance of this software for various soil, water, and crop conditions under pressurised irrigation systems (e.g., Assouline et al, 2006;Ajdary et al, 2007;Patel and Rajput, 2008;Phogat et al, 2012Phogat et al, , 2013Ramos et al, 2012).…”
Section: Soil Water Distribution and Water Balancementioning
confidence: 73%
“…HYDRUS 2D/3D (Šimůnek et al, 2008, 2011) has been used extensively for evaluating the effects of soil hydraulic properties, soil layering, dripper discharge rates, irrigation frequency and quality, timing of nutrient applications on wetting patterns and solute distribution (e.g., Cote et al, 2003;Gärdenäs et al, 2005;Assouline et al, 2006;Hanson et al, 2006;Ajdary et al, 2007;Patel and Rajput, 2008;Šimůnek and Hopmans, 2009;Phogat et al, 2009Phogat et al, , 2010Phogat et al, , 2012Phogat et al, , 2013Li and Liu, 2011;Ramos et al, 2012) because it has the capability to analyse water flow and nutrient transport in multiple spatial dimensions (Cote et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of Hydrus-2D for simulating the water transfer process under drip irrigation has been widely demonstrated on bare and cultivated soils (Vrugt et al, 2001;Skaggs et al, 2004;Assouline et al, 2006;Arbat et al, 2008;Patel and Rajput, 2008). The ability of this model for simulating the water transfer process for the corn case at Lavalette has been widely demonstrated in Mailhol et al (2001), Wöhling and Mailhol (2007) for furrow irrigation, and by Mubarak et al, (2009b) for DI.…”
Section: Modelling With Hydrus-2dmentioning
confidence: 99%
“…Short duration (10 to 24 hr) modelling studies [1,2] found that pulsed irrigation produced similar water content regimes to micro drip and slightly increased the wetted radius and depth compared with continuous irrigation. However, Elmaloglou and Diamantopoulos [3] reported a deeper wetting front for pulsed than for continuous irrigation with the same application depth.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to some technical limitations (e.g. discharge and operation pressure, clogging) application of low discharge rates is problematic [1]. There are spatial and application interventions that can be used in drip irrigation, such as pulsing of water, which may produce similar moisture and solute distribution in the soil to using low discharge rates.…”
Section: Introductionmentioning
confidence: 99%